A Research on The Vegetation Structures of The Rangelands of District Tufanbeyli, Adana - Çınar, Selahattin; Hatipoğlu, Rüştü; Avcı, Mustafa; Yücel, Celal; İnal, İlker (KAHRAMANMARAS SUTCU IMAM UNIV REKTORLUGU, 2019)
This research was conducted to determine vegetation structures of the upland rangelands in the five villages of Tufanbeyli district, Adana, in 2010. Vegetations of the rangelands were studied by the loop method. In the study, plant cover percentages, botanical compositions based on the cover percentage in the plant covered area, range quality values and range conditions of the rangelands studied were determined. Average percentages of grasses, legumes and other family plants in the total plant cover were determined as 36.9 %, 22.0 % and 41.1 %, respectively. It was determined that the averaged percentages of decreasing, increasing and invasive species were 20.9, 11.2 % and 67.2 %, respectively. The calculated quality values of rangelands ranged from 2.40 to 3.92, indicating that the range conditions of all rangelands studied were poor. Results indicated that grazing on the rangelands studied or on those having the same ecological conditions with the studied rangelands must be controlled, and improved by one of the range improvement methods such as over sowing, sowing or natural regeneration, alone or with the combinations of the other rangeland improvement methods. Nevertheless, new research must be conducted to determine the most proper methods of range improvement for the mentioned rangelands.
Keywords: Rangeland; Plant cover percentage; Botanical composition; Rangeland condition